Dynamic Characteristics of Horizontal Drilling with Flexible Drill String Based on ABAQUS Explicit Dynamics - Liu Xin Huang Zhongwei Wu Xiaoguang Li Gensheng Shi Huaizhong Wang Jiarui Wang Minghao; Huang Zhongwei; Wu Xiaoguang; Li Gensheng; Shi Huaizhong; Wang Jiarui; Wang Minghao (Shiyou jixie, 2025)
During the drilling of ultrashort-radius radial horizontal well with flexible drill string， the vertical shift of wellbore trajectory affects the encountering rate of target points. To reveal the dynamic characteristics of horizontal drilling with flexible drill string and reduce the vertical shift of wellbore trajectory， a horizontal drilling model of flexible drill string was built based on ABAQUS explicit dynamics and calculations were carried out subsequently. The research focuses on the motion of flexible drilling string， bit attitude， rock breaking characteristics， trajectory deviation characteristics， formation adaptability and the sensitivity of trajectory and overcut to weight on bit （WOB）. The research results show that the process of drilling with flexible drill string exhibits a spiral motion posture， rotating around the borehole axis while rotating around its own axis. The bit breaks rocks in an approximately conical scanning posture， and the process of breaking rocks has asymmetry. The field test verifies the accuracy of the model， and the trajectory deviation of flexible drill string mainly occurs in the gravity direction， explaining the reason for the vertical trajectory deviation in the field test. The corresponding trajectory deviation rates in soft， medium and hard rocks are 4.44%， 3.71% and 3.52% respectively， and are higher under high WOB conditions. An increase in WOB reduces the bit lateral aggressivity and overcut， and the preferred WOB for horizontal drilling is （30±5） kN. The research results provide a feasible solution to the study of the motion of flexible drill string.